Translation of WNT developmental programs into stem cell replacement strategies for the treatment of Parkinson's disease. (9th July 2017) - Toledo, Enrique M; Gyllborg, Daniel; Arenas, Ernest
Abstract : Wnt signalling is a highly conserved pathway across species that is critical for normal development and is deregulated in multiple disorders including cancer and neurodegenerative diseases. Wnt signalling is critically required for midbrain dopaminergic (mDA) neuron development and maintenance. Understanding the molecular processes controlled by Wnt signalling may thus hold the key to understand the physiopathology and to develop novel therapies aimed at preventing the loss of mDA neurons in Parkinson's disease (PD). Pharmacological tools to activate Wnt signalling have been used to translate in vivo developmental processes into protocols for the generation of bona fide mDA neurons from human pluripotent stem cells. Moreover, these protocols are currently being fine‐tuned to generate mDA neurons for clinical trials in PD. At the same time, a vast amount of molecular details of Wnt signalling continues to emerge and remains to be implemented into new protocols. We hereby review novel pharmacological tools to activate Wnt signalling and how single‐cell RNA‐sequencing is contributing to unravel the complexity of this pathway in the developing human ventral midbrain, generating novel hypotheses and identifying new players and opportunities to further improve cell replacement therapy for PD. Linked Articles: This article is part of a themed section on WNT Signalling: Mechanisms and Therapeutic Opportunities. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.24/issuetoc